Strawberry Vein Banding Virus Movement Protein P1 Interacts With Light-Harvesting Complex II Type 1 Like of Fragaria vesca to Promote Viral Infection - Xu, Shiqiang; Zhang, Xiangxiang; Xu, Kai; Wang, Zhanqi; Zhou, Xueping; Jiang, Lei; Jiang, Tong (Frontiers in Microbiology, 2022)
Chlorophyll a/b-binding protein of light-harvesting complex II type 1 like (LHC II-1L) is an essential component of photosynthesis, which mainly maintains the stability of the electron transport chain. However, how the LHC II-1L protein of Fragaria vesca (FvLHC II-1L) affects viral infection remains unclear. In this study, we demonstrated that the movement protein P1 of strawberry vein banding virus (SVBV P1) interacted with FvLHC II-1L in vivo and in vitro by bimolecular fluorescence complementation and pull-down assays. SVBV P1 was co-localized with FvLHC II-1L at the edge of epidermal cells of Nicotiana benthamiana leaves, and FvLHC II-1L protein expression was upregulated in SVBV-infected F. vesca. We also found that FvLHC II-1L effectively promoted SVBV P1 to compensate for the intercellular movement of movement-deficient potato virus X (PVXΔP25) and the systemic movement of movement-deficient cucumber mosaic virus (CMVΔMP). Transient overexpression of FvLHC II-1L and inoculation of an infectious clone of SVBV showed that the course of SVBV infection in F. vesca was accelerated. Collectively, the results showed that SVBV P1 protein can interact with FvLHC II-1L protein, which in turn promotes F. vesca infection by SVBV.